Analisis Perbandingan Kinerja Keuangan Bank Sebelum dan Sesudah Penerapan Quick Response Code Indonesian Standard - Andi Devita Damayanti; Nurdin (UNISBA Press, 2023)
Abstract. Quick Response Code Indonesian Standard or commonly abbreviated as QRIS is a unification of various types of QR from various Providers. All Payment System Service Providers who will use the QR Code for Payment must implement QRIS. The purpose of this study is to analyze the comparison of financial performance at Bank Rakyat Indonesia before and after the implementation of the Quick Response Code Indonesian Standard in the 3 year period before (2015-2018) and 3 years after (2019-2022). This research uses different tests Wilcoxon Signed Ranked Test, Paired Sample Test using SPSS 23, Microsoft Excel and collection techniques using purposive sampling. The research results obtained show that the value development before implementing the Indonesian Standard Quick Response Code has increased and decreased in each period, there has been an increase in the value of BOPO, and CAR after implementing the Indonesian Standard Quick Response Code while the LDR and ROA values ​​have decreased and there is a difference between bank's financial performance before and after the implementation of the Indonesian Standard Quick Response Code. There was an increase in the BOPO value of 72.13% and CAR of 21.68% after implementing the Indonesian Standard Quick Response Code while LDR and ROA decreased by 86.87% for LDR and 3.06% for ROA after implementing the Quick Response Code Indonesian Standard Abstrak. Quick Response Code Indonesian Standard atau biasa disingkat QRIS adalah penyatuan berbagai macam QR dari berbagai Penyelenggara Semua Penyelenggara Jasa Sistem Pembayaran yang akan menggunakan QR Code Pembayaran wajib menerapkan QRIS. Tujuan dari penelitian ini adalah untuk menganalisis perbandingan kinerja keuangan pada Bank Rakyat Indonesia sebelum dan sesudah penerapan Quick Response Code Indonesian Standard pada periode 3 tahun sebelum (2015-2018) dan 3 tahun sesudah (2019-2022). Penelitian ini menggunakan uji beda Wilcoxon Signed Ranked Test, Paired Sample Test dengan menggunakan SPSS 23, Microsoft Excel dan teknik pengumpulan menggunakan purposive sampling. Hasil penelitian yang diperoleh menunjukkan bahwa perkembangan nilai sebelum menerapkan Quick Response Code Indonesian Standard mengalami kenaikan dan penurunan di setiap periodenya, terjadi peningkatan nilai pada BOPO, dan CAR sesudah menerapkan Quick Response Code Indonesian Standard sedangkan nilai LDR dan ROA mengalami penurunan nilai dan terdapat perbedaan antara kinerja keuangan bank sebelum dan sesudah penerapan Quick Response Code Indonesian Standard. Terjadi peningkatan pada nilai BOPO sebesar 72,13% dan CAR sebesar 21,68% sesudah menerapkan Quick Response Code Indonesian Standard sedangkan LDR dan ROA mengalami penurunan nilai sebesar 86,87% untuk LDR dan 3,06% untuk ROA sesudah menerapkan Quick Response Code Indonesian Standard.